Chapter Marco Polo returns to China: Giuliano Montaldo's TV series (1982) - LEPRI, CHIARA (Studi e saggi, 2023)
In 1982, the Italian television network RAI produced a TV series by Giuliano Montaldo on the travels of the Venetian merchant Marco Polo. Broadcast in forty-six countries, the Emmy Award-winning cinematic project, which involved partners from the United States, Japan, Germany, and France, stood as the first film co-production between Italy and China and represented a relevant step in the consolidation of the Sino-Italian friendship after the establishment of diplomatic relations in 1970. This paper aims to research the transnational dynamics enacted by Marco Polo during the Sino-Italian co-production and presents the making of the TV series in China from ideation to distribution. The study includes an original interview with the director Montaldo (2022).